Protective effect of curcumin on fertility of rats after exposure to compact fluorescent lamps: An experimental study - Naser Khalaji; Mahshid Namyari; Yousef Rasmi; Masoumeh Pourjabali; Leila Chodari (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Testicular function is modified by maturational gonadostatic control highly susceptible to negative physiologic niche-altering factors like UV-rays. Objective: This study was performed in order to uncover new aspects of Compact Florescent Lamps (CFLs) induced damages on the testicular tissue of rats and evaluating the effect of curcumin on testis of rats after exposure to compact florescent Lamps. Materials and Methods: Twenty-four adult male Albino rats were randomly divided into three groups: control group (ethyl oleate 0.2 ml, IP, for 45 days, without CFLs exposure), fluorescent group (ethyl oleate 0.2 ml, IP, daily and treated with 12 hr CFLs exposure for 45 days) and curcumin group (curcumin 20 μ M, IP along with 12 hr CFLs exposure for 45 days). The rats were anesthetized at the end of the experiment. Gonadotropin hormones and prolactin levels were measured; Histopathological and histomorphometrical analysis of the testis was carried out. Results: Results of this study showed that CFLs significantly decreased serum levels of follicle stimulating hormone, prolactin, testicular weight, sperm motility, TDI, and SPI. Furthermore, CFLs had no effect on serum levels of luteinizing hormone and sperm count and also, increased abnormal sperm shapes. Our results also showed that curcumin supplementation following CFLs reversed these alterations. Conclusion: These results strongly suggest that CFLs severely impairs testis while curcumin as an antioxidant had protective effects on undesirable effects in testis induced by CFLs